METHODS OF USING GAMING TECHNOLOGIES IN TEACHING A FOREIGN LANGUAGE AT SCHOOL - Utemuratova Khilola Telmanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In recent years, there has been a growing interest in incorporating gaming technologies into educational settings,particularly in the field of foreign language teaching. This emerging trend stems from the recognition that traditional teaching methods may not always fully engage and motivate students, resulting in limited language acquisition outcomes. As such, educators and researchers have started exploring the potential benefits of integrating gaming technologies as a means to enhance language learning experiences in schools.